Creative attitude in a group of youths gifted in the domain of science subjects - Monika Sztolpa; Aleksandra Lewandowska-Walter; Małgorzata Lipowska (Current Issues in Personality Psychology, 2016)
Background We attempted to assess whether students identified by their teachers as gifted in the domain of science are characterised by significantly higher levels of intelligence and creativity than other students. We investigated the features of their personalities that are indicators of their exhibited creative or reproductive attitude in the cognitive and the motivational domains. As a consequence, criteria will be developed for identifying gifted students.